Pendekatan Inovatif terhadap Praktik Manajemen Sumber Daya Manusia Berbasis Komunitas Desa Toapaya Selatan Toapaya Bintan - Hartoto, Hartoto; Prihantini, Prihantini; Rosid, Abdul; Sofyan, Hady (CV. Creative Tugu Pena, 2024)
The implementation of an innovative approach in community-based Human Resources (HR) management in Toapaya Selatan Village, Toapaya, Bintan, has had a significant and diverse impact on the local community. These impacts include increasing welfare, strengthening social ties, empowering women, local economic growth, improving quality of life, community participation, capacity development, and collaboration opportunities. This approach has improved household incomes and created new job opportunities, as well as helping to reduce operational costs and increase business efficiency, thereby increasing the competitiveness and sustainability of the village economy. In addition, through this innovative approach, public awareness of the importance of a healthy lifestyle and good environmental sanitation increases, reducing disease rates and improving the overall health and well-being of society. Community participation and involvement in decision making that affects their lives has also increased, giving them a sense of ownership and responsibility in the development of their own villages. In addition, developing the capacity of local communities and institutions in community-based HR management opens up opportunities for collaboration and network development with external parties such as educational institutions, local governments and non-governmental organizations. Overall, investment in innovative and community-based HR management practices can be an effective instrument in sustainable development and improving community welfare. Keywords: Human Resource Management Practices, Innovative Approach